Comparative Spectral Analysis and Correlation Properties of Observed and Simulated Total Column Ozone Records - Viktória Homonnai; Imre M. Jánosi; Franck Lefèvre; Marion Marchand (Atmosphere, 2013)
We present a statistical analysis of total column ozone records obtained from satellite measurements and from two global climate chemistry models on global scale. Firstly, a spectral weight analysis is performed where the relative strength of semiannual, annual and quasi-biennial oscillations are determined with respect to the integrated power spectra. The comparison reveals some anomalies in the model representations at each spectral component. The tails of the spectra demonstrate that both models underestimate high frequency (daily) ozone variability, which might have a complex origin, since several dynamical processes affect short time changes of the ozone level at a given location. Secondly, detrended fluctuation analysis is exploited to analyze two-point correlations of anomaly time series. Both models reproduce the characteristic geographic dependence of correlation strength over the overlapping area with empirical observations (latitude band between 60°S and 60°N). The values of precise correlation exponents are hard to obtain over regions where quasi-biennial oscillations or other strong nonstationarities (ozone hole) are present. In spite of all the numerical difficulties, significant long range correlations are detected for total ozone over all geographic locations.